Programming Conventions - Halpin, Terry; Rugaber, Spencer (Taylor & Francis Group, 2015)
The LogiQL language and compiler give a great deal of latitude to programmers to express their ideas. In particular, the choice of names, capitalization, and use of whitespace and comments are relatively unconstrained. Nevertheless, there are some advantages to using uniform conventions: Programs become more readable, errors are more easily detected, and training is facilitated. This appendix describes the set of conventions used in this book. First, a descriptive overview is given, and then summary lists are provided